Coexistence of iron deficiency and thalassemia trait: a study in antenatal females - Arora, Sheetal; Rana, Deepshikha; Raychaudhuri, Sujata; Dhupia, J. S. (International Journal of Research in Medical Sciences, 2017)
Background: Thalassemia is most common genetic disorder worldwide and about 7% of world population is carrier. The prevalence of Beta thalassemia trait (BTT) is 3.5–10% in India. The National Family Health Survey (NFHS-3) of 2011 reveals the prevalence of iron deficiency anemia (IDA) as 70–80% in children, 70% in pregnant women, and 24% in adult men. As both of them are close differential diagnosis and both can coexist together, this study aims to detect hemoglobinopathies in pregnant women and quantify the effect of iron deficiency on HbA2 levels in order to improve the detection of β thalassemia trait with and without iron deficiency. Methods: Hb, RBC indices, and peripheral smears of 90 pregnant females with microcytic hypochromic blood picture were studied. Serum ferritin and HPLC (High Performance Liquid Chromatography) was performed. The results were analysed statistically by using SPSS version 16.0. Results: 93.3% patients had HbA2 <2%, 4.44% had >4.0% which characterise BTT and remaining 2.22% had between 3.0%-4.0%. HbA2 <2.0% may be seen in IDA, ATT, HbH disease and Delta thalassemia. 91.11% had reduced serum ferritin and 2.22% had normal ferritin levels. Conclusions: This study reveals that there is frequent occurrence of iron deficiency anaemia in patients with thalassemia traits. This can substantially invalidate the diagnosis of the latter. Hence, iron deficiency should be identified and rectified in patients with suspicion of thalassemia trait.